Tires and vertical dynamics of wheeled mobile driving simulators. (February 2019) - Zöller, Chris; Wagner, Paul; Winner, Hermann
Highlights: Determination of force and vertical dynamics characteristics of solid tires. Comparison of energy consumption between solid and pneumatic tires. Analysis of tire impact on acceleration representation by motion control. Investigation of subject immersion disturbance by road excitation. Abstract: Wheeled Mobile Driving Simulators (WMDS) promise a high potential for urban traffic simulation. The tires generate the accelerations of WMDS and therefore are a key component of this simulator type. Hence, the choice of a proper tire concept is of high importance. Solid tires with compact dimensions and a high vertical stiffness are a possible alternative approach to conventional pneumatic tires. To assess the application potential of solid tires their characteristics are identified. The results show that high slip values and slip angles are necessary to reach the maximum friction coefficient of about 0.8 while their correlation is highly nonlinear. With the identified tire properties, the impact of the tires on energy consumption and motion control performance of WMDS is investigated. The solid tires show an increased energy consumption of about 4% compared to pneumatic tires in representative urban driving cycle simulations. Solid tires with their nonlinear characteristics lead to five times higher lateral acceleration errors in relation to pneumatic tires at accelerations of 5 m/s 2 during a horizontal eight maneuver. The vertical properties of both tires were identified to be not sufficient for the application of a WMDS solely sprung by tires on uneven grounds of common quality.